2017
DOI: 10.3847/1538-4357/aa9120
|View full text |Cite
|
Sign up to set email alerts
|

The Outer Halo of the Milky Way as Probed by RR Lyr Variables from the Palomar Transient Facility*

Abstract: RR Lyrae stars are ideal massless tracers that can be used to study the total mass and dark matter content of the outer halo of the Milky Way (MW). This is because they are easy to find in the light-curve databases of large stellar surveys and their distances can be determined with only knowledge of the light curve. We present here a sample of 112RR Lyr stars beyond 50 kpc in the outer halo of the MW, excluding the Sgr streams, for which we have obtained moderate-resolution spectra with Deimos on the Keck II … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
48
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(57 citation statements)
references
References 92 publications
(170 reference statements)
5
48
1
Order By: Relevance
“…Curiously, only the measurement by Xue et al (2015) is in broad agreement with the results of Deason et al (2014). Both Slater et al (2016) and Cohen et al (2016Cohen et al ( , 2017 reported significantly shallower density profiles for the stellar halo between 50 and 100 kpc.…”
Section: Introductionsupporting
confidence: 65%
See 1 more Smart Citation
“…Curiously, only the measurement by Xue et al (2015) is in broad agreement with the results of Deason et al (2014). Both Slater et al (2016) and Cohen et al (2016Cohen et al ( , 2017 reported significantly shallower density profiles for the stellar halo between 50 and 100 kpc.…”
Section: Introductionsupporting
confidence: 65%
“…However, there exists a small number of stars that travel to the periphery (and perhaps even one step beyond) of the Milky Way which, if detected, can be used as tracers of its extent. In particular, in the past decade, there have been several attempts to expand upon the inventory of these outer halo denizens (see e.g., Brown et al 2010;Deason et al 2012;Bochanski et al 2014;Huxor & Grebel 2015;Cohen et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…It is important to remember that our sample selection procedure that we apply to the Pan-STARRS1 3π database takes advantage of the experience gained by attempting to use the SDSS (Sesar et al 2007(Sesar et al , 2010 and then to analyze the more difficult PTF (Cohen et al 2017) with few observations taken with a random cadence. Our PS1 sample of RRab stars ) is unique in that it contains a large number (44,403) of RR Lyrae in total, of which 17,452 lie within the radial range of R gc from 20 up to 130 kpc, all with highly precise photometry.…”
Section: Comparison With Previous Resultsmentioning
confidence: 99%
“…There have also been efforts to reach the outer halo using blue horizontal branch (BHB) stars, which to first order have a fixed luminosity similar to that of RRab (see, e.g., Deason et al 2014), but these run into problems of confusion with much more numerous blue stragglers at the same apparent magnitude and with quasars. Prior to the present work, perhaps the most successful attempt to probe the density distribution in the outer Galactic halo was by Cohen et al (2017), reaching out to above 100 kpc, with a small (∼450) sample of RRab stars selected from the Palomar Transient Facility (PTF) database.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation